Penampilan Produksi Ayam Broiler yang Diberi Bacillus circulans dan Bacillus sp. Selama Periode Pemulihan Setelah Pembatasan Ransum - A Azis; F Manin; . Afriani (Faculty of Animal Science, Bogor Agricultural University, 2010)
The present study was designed to investigate the efficacy of Bacillus circulans and Bacillus sp. as probiotic during realimentation period on performance of broiler chickens. Three hundred of 7 days-old unsexed broiler chicken of Cobb commercial strain were used in the experiment. The treatments were: control ration was fed ad libitum (P-0), ration with energy restriction at 1.5xBW0.67EM kcal/day without (P-1) and with (P-2) probiotic supplementation during realimentation period, and ration with energy restriction at 2.25xBW0.67EM kcal/day without (P-3) and with (P-4) probiotic supplementation during realimentation period. Feed restriction was applied from 7 to 14 days of age. The experiment was arranged as a completely randomized design with 5 treatments and 6 replications. The results showed that feed intake and body weight gain of chickens submitted to early feed restriction on P-1, P-2, P-3 and P-4 were significantly lower (P < 0.05) than that of chicken fed control diet. During realimentation period, body weight gain of chicken given P-1 and P-2 was lower (P < 0.05) than those obtained from P-3, P-4 and P-0 from 14 to 28 days of age. Compensatory growth only occur during the 28 to 35 days of age on P-4 and had similar performance with control at age of 42 days. It was concluded that energy restriction 2.25xBW0.67EM kcal/day for 7 days (7 to 14 days of age) with supplementation of probiotic B. circulans and Bacillus sp. (P-4) during realimentation period showed similar compensatory growth and body weight, but production index and feed cost better than control. Key words: feed restriction, probiotic, realimentation